I followed the step by step outline in my textbook to solve this equation, but I still got it wrong.
Could you please tell me where I went wrong and how to fix it?
Thank you!
Hello, positiveion!
How did you get 40 and 18 ?
$\displaystyle \begin{bmatrix}x\\y\end{bmatrix} \:=\:\tfrac{1}{13}\begin{bmatrix}2&3\\\text{-}3&2\end{bmatrix}\begin{bmatrix}3\\11\end{bmatrix } \;=\; \tfrac{1}{13}\begin{bmatrix}2(3) + 3(11) \\ \text{-}3(3) + 2(11) \end{bmatrix}$ . $\displaystyle = \;\tfrac{1}{13}\begin{bmatrix}39 \\ 13\end{bmatrix} \;=\;\begin{bmatrix}3\\1\end{bmatrix}$